Evaluating Treatment Tolerability in Cancer Clinical Trials Using the Toxicity Index. (24th February 2020) - Gresham, Gillian; Diniz, Márcio A; Razaee, Zahra S; Luu, Michael; Kim, Sungjin; Hays, Ron D; Piantadosi, Steven; Tighiouart, Mourad; Yothers, Greg; Ganz, Patricia A; Rogatko, André
Abstract: Background: The National Cancer Institute Moonshot research initiative calls for improvements in the analysis and reporting of treatment toxicity to advise key stakeholders on treatment tolerability and inform regulatory and clinical decision making. This study illustrates alternative approaches to toxicity evaluation using the National Surgical Adjuvant Breast and Bowel Project R-04 clinical trial as an example. Methods: National Surgical Adjuvant Breast and Bowel Project R-04 was a neoadjuvant chemoradiation trial in stage II–III rectal cancer patients. A 2 x 2 factorial design was used to evaluate whether the addition of oxaliplatin (Oxa) to 5-fluorouracil (5FU) or capecitabine (Cape) with radiation therapy improved local-regional tumor control. The toxicity index (TI), which accounts for the frequency and severity of toxicities, was compared across treatments using multivariable probabilistic index models, where Pr A < B indicates the probability that higher values of TI were observed for A when compared with B. Baseline age, sex, performance status, body mass index, surgery type, and stage were evaluated as independent risk factors. Results: A total of 4560 toxicities from 1558 patients were analyzed. Results from adjusted probabilistic index models indicate that oxaliplatin-containing regimens had statistically significant ( P  < .001) probability (Pr) for higher TI compared with regimens without oxaliplatin (Pr 5FU < 5FU + Oxa = 0.619, 95% confidence interval [CI] = 0.560 to 0.674; Pr 5FU < Cape + Oxa = 0.627, 95% CI = 0.568 to 0.682; Pr Cape < 5FU + Oxa = 0.587, 95% 0.527 to 0.644; and Pr Cape < Cape + Oxa = 0.596, 95% 0.536 to 0.653). When compared with other existing toxicity analysis methods, TI provided greater power to detect differences between treatments. Conclusions: This article uses standard data collected in a cancer clinical trial to introduce descriptive and analytic methods that account for the additional burden of multiple toxicities. These methods may provide a more accurate description of a patient's treatment experience that could lead to individualized dosing for better toxicity control. Future research will evaluate the generalizability of these findings in trials with similar drugs.